Reduction in Muscle Fiber Force Production, Disruption of Muscle Cell Architecture and Accumulation of Fatty Macrophages in Patients with Chronic Rotator Cuff Tears - Bedi, Asheesh (Orthop J Sports Med, 2013)
OBJECTIVES: A common pathophysiological change that occurs in torn rotator cuff muscles is atrophy of muscle fibers and an accumulation of intramuscular fat, collectively referred to as "fatty degeneration." For many patients with chronic rotator cuff tears that undergo surgical repair, fatty degeneration is not resolved. The etiology of fatty degeneration has not been characterized in humans, and gaining greater insight into the mechanisms that lead to the development of atrophy and fat accumulation will likely improve the recovery of patients who undergo surgical repair of a torn rotator cuff. The purpose of this study was to gain a greater understanding of the changes in muscle fiber contractility, myofibril architecture and fat accumulation in patients with rotator cuff tears. We hypothesized that torn rotator cuff muscles have reduced muscle fiber force production, disordered myofibrils and an accumulation of fat vacuoles and lysosomes. METHODS: This study was approved by our institution's IRB. Prior to enrollment in the study, informed consent was obtained from patients with a full thickness supraspinatus tear as verified by MRI or ultrasound by a fellowship-trained musculoskeletal radiologist. Biopsies of the supraspinatus and anterior deltoid were obtained at the time of repair and prepared for muscle contractility testing or microscopy. The contractility of permeabilized muscle fibers was performed as previously described, and force values of torn supraspinatus and intact deltoid muscles were compared to age-matched force values of healthy fibers sampled from the vastus lateralis muscle in a previous study. Scanning electron micrographs and immunohistochemistry were also performed on select muscle biopsies. RESULTS: Compared with healthy muscle fibers from the vastus lateralis, there was a 29% reduction in specific force (maximum isometric force normalized to fiber cross-sectional area) in torn supraspinatus muscles, and a 34% reduction in specific force for deltoid muscle fibers (Figure 1A, P<0.05). Numerous large intramuscular lipid vacuoles and lysosomes were observed in areas of myofibril degradation (Figure 1B) and streaming of force transmitting Z-disks was often present (Figure 1C). Fatty macrophages, also known as foam cells, were also observed in the ECM between muscle fibers in electron micrographs (Figure 1D) and using a macrophage/foam cell surface marker and BODIPY fluorescent lipid stain (Figure 1E). CONCLUSION: Combined, these results identify chronic structural and mechanical changes in torn rotator cuff muscles that may explain the poor functional capacity of the muscles after repair. While the supraspinatus muscle had reduced force production, a reduction in force was also noted in the deltoid which may parallel symptomatic rotator cuff disease. Further, the accumulation of fat in large lipid vacuoles and high lysosome densities near myofibrils suggest that a portion of the intramyocellular fat that accumulates in torn cuff muscles likely comes as a result of myofibril degradation. We have also identified for the first time that a portion of the extramyocellular fat in torn rotator cuff muscles accumulates in fatty macrophages/foam cells. Future therapies that target lysosomal-mediated myofibril degradation or macrophage accumulation may help to ameliorate the severity of fatty degeneration in patients with rotator cuff tears.